Masochistic Fun with Plutocratic Murder - Blair Fix (Economics from the Top Down, 2023)
There's nothing like waking up to a boatload of Twitter scorn. It's refreshing, in a masochistic sort of way. Some backstory. After most of my blog posts, I put the charts on Twitter, usually with a provocative caption. (It's more fun that way.) So after last week's review of Cory Doctorow's book Red Team Blues, I tweeted the relation between income inequality and the rate of murder. The next morning my Twitter feed was … interesting. The tweet apparently went viral, helped along by a nice little insult from Nassim Nicholas Taleb: 'No. The statement by that fettuccinibrain is contradicted by his own graph. #fooledbyrandomness'. Apart from him calling me a fettuccini brain, I have a lot of respect for Taleb, who's famous for (among other things) his excellent book Fooled By Randomness. It's an engaging romp through the many ways that human's get duped by random patterns. Back to the tweet. Taleb is implying that the relation between inequality and murder is essentially a random blob of data, and that I'm a fool to plot a trend line through it. I disagree.
Keywords: P1; C1; D3; K; 330; crime; income distribution; inequality; methodology; murder